Emodin repairs interstitial cells of Cajal damaged by cholelithiasis in the gallbladder - Zhen-peng Huang; Hu Qiu (Frontiers Media S.A., 2024)
BackgroundHypercholesterolemia induces cholelithiasis and dysfunction of gallbladder motility. Interstitial cells of Cajal (ICCs) contribute to gallbladder motility. Emodin modulates the contractility of the gallbladder muscle; however, the underlying mechanism is unknown.AimThis study aimed to explore the effects of emodin on gallbladder ICCs with cholelithiasis in a guinea pig model.MethodsAnimals were randomly divided into a healthy control group and three study groups. All study groups received a high-cholesterol diet (HCD) for 8 weeks. Subsequently, they were randomly assigned to either the HCD group or one of the emodin treatment groups lasting 4 or 8 weeks. Total cholesterol (TC) and triglycerides (TG) were measured to determine changes in serum lipid levels. Immunohistochemistry was performed to detect the morphology and number of ICCs. TUNEL assays were performed to detect ICC apoptosis. Transmission electron microscopy was employed to observe ICC structure. Western blotting and real-time polymerase chain reaction were used to detect changes in stem cell factor (SCF)/c-kit pathway expression.ResultsSerum TC and TG were higher in all study groups. In cases of cholelithiasis, the SCF/c-kit pathway was downregulated, the number of gallbladder ICCs decreased, apoptosis increased, and the ICC network structure was damaged. After emodin treatment, the SCF/c-kit pathway was upregulated, the number of gallbladder ICCs increased, apoptosis decreased, and the ICC network structure recovered.ConclusionCholelithiasis downregulates the SCF/c-kit pathway and damages gallbladder ICCs. Emodin upregulates the SCF/c-kit pathway and increases gallbladder ICCs, contributing to recovery from gallbladder motility disorders.\